HASIL KONFERENSI KEPENDUDUKAN DI KAIRO: IMPLIKASINYA PADA PROGRAM KESEHATAN REPRODUKSI DI INDONESIA - Siswanto Agus Wilopo (Populasi, 1994)
The World PopulationConference in Cairo has received substantial attention and comments from the mass media and a large circle of experts, although a more basic explanation is still needed due to the result of the conference. Since abortion is considered a very important issue which dominates the field of reproductive health, it needs to further analyze the relations between abortion and the 'new concept' of reproductive health. This paper broadly analyzes the objectives and the agreed result of the conference. It also proposes several implications on the reproductive health program in Indonesia. Even though, as the mass media reported, the Cairo Conference seemed to be a conference on abortion, the theme of the conference was: Population, Sustainable Economic Growth, and Sustainable Development. Indonesia takes a very active role in the preparation of the world's population conference, including to conduct and initiate the summit population conference of the Non-Aligned Ministerial level prior the Cairo Conference. The Cairo World Population Conference has resulted in a substantially broad Population Action Program, in which the implementation needs serious consideration on the heterogeneity of the respective countries according to the priorities of development, cultural considerations, norms, religion, and law that prevails in the respective countries, yet the Conference should consider the norms of the universal human rights. Out of various materials covered in the Population Action Program, reproductive health problems have become one of the important controversial sources. For this reason it has thus been agreed to accept a "new concept" of reproductive health. Out of this 'new concept', some implications of several reproductive health programs emerge, particularly the family planning program of the countrywhich should be expanded and qualified. Even though the "new concept" of reproductive health covers sexual reproductive rights, it has been wholly agreed that abortion would not be promoted as one of the implementations of the family planning method. The target of quantity in various fields could be optimistically achieved except the maternal mortalitydecline. Without a breakthrough effort in the new reproductive healthsector the quantitative aims to reduce the maternalmortality rate in Indonesia could never be achieved.